Preparation and characterization of spherical silica-porphyrin catalysts obtained by the sol-gel methodology - Papacidero, A. T.; Rocha, L. A.; Caetano, B. L.; Molina, E.; Sacco, W. C.; Nassar, E. J.; Martinelli, Y.; Mello, C.; Nakagaki, S.; Ciuffi, K. J. (Elsevier B.V., 2006)
This work describes the synthesis of a first-generation iron porphyrin catalyst entrapped in a silica matrix by the sol-gel route, leading to spherical particles. The catalyst was synthesized by the method of Stober, through hydrolysis and condensation of the alkoxysilane TEOS in a mixture of alcohol, water and ammonia, in the presence of the iron porphyrin Fe(TPP)Cl. The relation between particle morphology and catalytic activity of the different Fe(TPP)-SiO2, obtained using different H2O/silane molar ratios and ammonia concentrations in the xerogel syntheses, was studied.The obtained catalysts were characterized by UV-vis spectroscopy, NMR Si-29. thermogravimetric analysis and transmission electron microscopy. Their ability to catalyze (Z)-cyclooctene epoxidation and cyclohexane oxidation was tested using iodosylbenzene as oxygen donor; the oxidation products were analyzed by gas chromatography and the catalysts obtained in a form of particles spherical and monodispersed showed to be a promising catalytic system for selective oxidation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: sol-gel; iron porphyrin; spherical particles; supported catalyst; catalysis; oxidation; silica